2016
DOI: 10.1103/physrevlett.117.037002
|View full text |Cite
|
Sign up to set email alerts
|

Momentum-Resolved Electronic Structure of the High-TcSuperconductor Parent CompoundBaBiO3

Abstract: We investigate the band structure of BaBiO_{3}, an insulating parent compound of doped high-T_{c} superconductors, using in situ angle-resolved photoemission spectroscopy on thin films. The data compare favorably overall with density functional theory calculations within the local density approximation, demonstrating that electron correlations are weak. The bands exhibit Brillouin zone folding consistent with known BiO_{6} breathing distortions. Though the distortions are often thought to coincide with Bi^{3+}… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
56
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 56 publications
6
56
1
Order By: Relevance
“…Interestingly, an early theory of the metal-insulator transition 43 in (RE)NiO 3 is very closely related to the neutral-ionic transition model. Finally, lower than formal charge has also been recognized recently in the perovskite BaBiO 3 , where again the true electron configuration of the Bi-ions is a homogenous Bi 3+ , as opposed to what was believed before, alternating Bi 3+ and Bi 5+ ions 47,48 . We will not only be interested in when negative charge-transfer gap is most likely, but whether there can occur a real transition from positive to negative charge-transfer gap.…”
mentioning
confidence: 82%
See 3 more Smart Citations
“…Interestingly, an early theory of the metal-insulator transition 43 in (RE)NiO 3 is very closely related to the neutral-ionic transition model. Finally, lower than formal charge has also been recognized recently in the perovskite BaBiO 3 , where again the true electron configuration of the Bi-ions is a homogenous Bi 3+ , as opposed to what was believed before, alternating Bi 3+ and Bi 5+ ions 47,48 . We will not only be interested in when negative charge-transfer gap is most likely, but whether there can occur a real transition from positive to negative charge-transfer gap.…”
mentioning
confidence: 82%
“…Then for |∆| > U d the system is a Mott-Hubbard insulator, for |∆| < U d the system is a charge-transfer insulator 32 . Note that the system remains a charge-transfer insulator even if the sign of ∆ is negative 41,42,44,47 . We will not only be interested in when this is most likely, but whether there can occur a real transition from positive to negative ∆.…”
Section: The Valence Transition Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…[6][7][8] Among Bi-containing oxides, perovskite BaBiO 3 ,i nw hich octahedral [BiO 6 ]b reathes out and in for Bi 3 + and Bi 5 + ,r espectively,h as long been investigated. [9][10][11] Previous investigationsh ave shown that under hole-doping conditions, such as in Ba 0.6 K 0.4 BiO 3 and BaBi 0.7 Pb 0.3 O 3 ,the breathing distortion is significantly suppressed, and this leads to as imple perovskite lattice in which superconductivity emerges. [12,13] In essence, such compositional engineering results in the modification of coordination environments of cations in the framework.…”
Section: Introductionmentioning
confidence: 99%